2016
DOI: 10.1088/0256-307x/33/4/046501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion and Deformation of Graphene

Abstract: Taking into consideration short-atomic-range interactions and anharmonic effects, we calculate the thermal expansion coefficients, Gruneisen parameters, the elastic modulus of graphene varying with temperature and the phonon frequency. The anharmonic effects associated with the graphene deformation are also discussed. The results show that the value of thermal expansion coefficient is negative in the moderate temperature range, and it becomes positive when the temperature grows to be higher than a certain valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Moreover, the Grüneisen parameter varies inversely with the bond strength of the material. 42,43 Therefore, the FM/AFM phases has weaker bonding interaction compared with the PM phase, which is in agreement with our aforementioned simulation results.…”
Section: Nanoscale Accepted Manuscriptsupporting
confidence: 91%
“…Moreover, the Grüneisen parameter varies inversely with the bond strength of the material. 42,43 Therefore, the FM/AFM phases has weaker bonding interaction compared with the PM phase, which is in agreement with our aforementioned simulation results.…”
Section: Nanoscale Accepted Manuscriptsupporting
confidence: 91%
“…The moray eel collected from Chinese waters were initially identified as G. reticularis according to the descriptions of previous reports ( Zhu et al 1962 , 1985 , Cheng and Zheng 1987 , Zhang et al 2010 , Chen and Zhang 2015 ), which included only simple external descriptions without vertebra number. The morphological analysis based on newly collected specimens in this study showed that the vertebra number ranged from 137 to 139, similar to that of G. minor (129–143) but obviously different from G. reticularis (114–126) ( Smith and Böhlke 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 37 species of the genus Gymnothorax exist, but G. minor has been reported rarely in China ( Chen and Zhang 2015 ), while G. reticularis is the widely used identification by Chinese ichthyologist. The Chinese name “Wang Wen Luo Xiong Shan” was assigned to the species “ Gymnothorax reticularis ”, which has been persistently confused with G. minor ( Zhu et al 1962 , 1985 , Cheng and Zheng 1987 , Zhang et al 2010 , Chen and Zhang 2015 ). In fact, both species can be easily distinguished by the number of vertebrae and their differing distribution ranges: the vertebrae number 129–143 in G. minor vs. 114–126 in G. reticularis ; G. minor is found from the northwestern to the southwestern Pacific vs. G. reticularis from the Indian Ocean to the Red Sea ( Smith and Böhlke 1997 , Kim et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, low-dimensional materials have aroused widespread research interest and show great application prospects. [1][2][3][4] Representatively, graphene, a two-dimensional nanomaterial composed of carbon atoms with sp 2 hybrid orbital hexagonal honeycomb lattice, has received continuous attention due to its many intriguing characteristics, such as superior thermal conductivity, [5][6][7][8][9] strong mechanical strength, [10,11] electronic properties, [12][13][14][15][16] and optical transparency. [17][18][19] In particular, due to the superior thermal conductivity (exceeding ∼ 3000 W/K•m near room temperature [6] ), graphene plays a growing significant role in the thermal management of the next generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%